2018
DOI: 10.1074/jbc.ra118.004763
|View full text |Cite
|
Sign up to set email alerts
|

Functional dissection of the N-terminal extracellular domains of Frizzled 6 reveals their roles for receptor localization and Dishevelled recruitment

Abstract: The Frizzled (FZD) proteins belong to class F of G proteincoupled receptors (GPCRs) and are essential for various pathways involving the secreted lipoglycoproteins of the wingless/ int-1 (WNT) family. A WNT-binding cysteine-rich domain (CRD) in FZDs is N-terminally located and connected to the seven transmembrane domain-spanning receptor core by a linker domain that has a variable length in different FZD homologs. However, the function and importance of this linker domain are poorly understood. Here we used sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
2
16
0
Order By: Relevance
“…Several amino residuals in intracellular loops 1, 2, and 3 and the flanking region near to intracellular loop 3 were also important for the intracellular location of Dishevelled while the mutant impaired the binding of Dishevelled [7377]. Research based on FZD6 also showed that the linker domain, especially some conserved cystines, between the CRD domain and seven transmembrane core was imperative for Dishevelled recruitment [78]. One potential mechanism for FZD4 activation would be a Wnt/Norrin-induced movement of the seventh transmembrane domain to expose the key FZD4-Dishevelled interaction site [79].…”
Section: Resultsmentioning
confidence: 99%
“…Several amino residuals in intracellular loops 1, 2, and 3 and the flanking region near to intracellular loop 3 were also important for the intracellular location of Dishevelled while the mutant impaired the binding of Dishevelled [7377]. Research based on FZD6 also showed that the linker domain, especially some conserved cystines, between the CRD domain and seven transmembrane core was imperative for Dishevelled recruitment [78]. One potential mechanism for FZD4 activation would be a Wnt/Norrin-induced movement of the seventh transmembrane domain to expose the key FZD4-Dishevelled interaction site [79].…”
Section: Resultsmentioning
confidence: 99%
“…DVL is a central mediator of the β-catenin-dependent and PCP-like WNT signaling pathways and its recruitment to FZD is an initial step in DVL-dependent signaling 12,47,48 . Simultaneous overexpression of DVL and FZD leads to FZD-dependent membrane recruitment of DVL even in the absence of a ligand [49][50][51] colocalization and recruitment of cytosolic DVL present in punctate aggregates to membrane-expressed FZDs 47,[49][50][51] . However, quantification of recruitment and measurement of ligandinduced dynamics were not possible.…”
Section: Sag13 Affects Fzd 6 -Dvl2mentioning
confidence: 99%
“…In order to assess ligand-induced effects on DVL-FZD BRET, we chose an acceptor:donor ratio corresponding to the plateau part of the saturation curves for both setups. In addition, we did not treat the cells with the porcupine inhibitor C59 to block secretion of endogenous WNTs as their presence had no significant effect on the basal recruitment of the overexpressed DVL2 to the overexpressed FZD 6 as recently reported 51 and presented in Supplementary Fig. 15a, b.…”
Section: Sag13 Affects Fzd 6 -Dvl2mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is still a mystery how the phosphoprotein dishevelled (DVL), which acts as a central signalling relay and FZD‐interacting scaffold in several β‐catenin‐dependent and β‐catenin‐independent WNT signalling pathways, biochemically mediates WNT‐induced and FZD‐mediated signal initiation and transmission – despite its polymerization in agonist‐induced signalosomes. Further, it remains unclear, if DVL interaction with FZDs is weakened or strengthened upon agonist stimulation in the light of conflicting findings . In this context, it remains obscure if DVL could act as a FZD binding partner to form a ternary complex in a pharmacological sense as previously hypothesized .…”
Section: Introductionmentioning
confidence: 95%